2017
DOI: 10.1371/journal.pone.0171861
|View full text |Cite
|
Sign up to set email alerts
|

Double strand RNA delivery system for plant-sap-feeding insects

Abstract: Double-stranded RNA (dsRNA)-mediated gene silencing, also known as RNA interference (RNAi), has been a breakthrough technology for functional genomic studies and represents a potential tool for the management of insect pests. Since the inception of RNAi numerous studies documented successful introduction of exogenously synthesized dsRNA or siRNA into an organism triggering highly efficient gene silencing through the degradation of endogenous RNA homologous to the presented siRNA. Managing hemipteran insect pes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 52 publications
0
76
0
Order By: Relevance
“…Targeting insects that feed internally (sap sucking and endophagous insects) with synthetic dsRNA requires a different strategy because spraying dsRNA solutionsx2 on plant surfaces is not effective against these species. A recent study used the plant vascular system to deliver dsRNA solutions via soil irrigation and trunk injection to target the sap‐sucking brown marmorated stink bug . The irrigation and trunk injection of the vitellogenin‐A1 and juvenile hormone acid O‐methyltransferase dsRNAs showed 35–40% mortality in brown marmorated stink bugs .…”
Section: Strategies For Oral Administration Of Dsrna In Insects and Imentioning
confidence: 99%
“…Targeting insects that feed internally (sap sucking and endophagous insects) with synthetic dsRNA requires a different strategy because spraying dsRNA solutionsx2 on plant surfaces is not effective against these species. A recent study used the plant vascular system to deliver dsRNA solutions via soil irrigation and trunk injection to target the sap‐sucking brown marmorated stink bug . The irrigation and trunk injection of the vitellogenin‐A1 and juvenile hormone acid O‐methyltransferase dsRNAs showed 35–40% mortality in brown marmorated stink bugs .…”
Section: Strategies For Oral Administration Of Dsrna In Insects and Imentioning
confidence: 99%
“…Consistent with the central role of dsRNA in triggering RNAi, numerous studies have shown that plants treated with virus‐specific dsRNA or single‐stranded RNA (ssRNA) molecules that fold into hairpin conformation showed antiviral resistance (Carbonell et al ., ; Gan et al ., ; Konakalla et al ., ; Tenllado and Diaz‐Ruiz, ; Tenllado et al ., ,b; Yin et al ., ). dsRNAs were also shown to be effective against fungi (Koch et al ., ; Wang et al ., , ) and insects (Baum et al ., ; Ghosh et al ., ; Li et al ., ; Luo et al ., ), thus providing important implications for dsRNA‐triggered RNAi as an emerging novel approach for crop protection. RNAi has been deployed for plant protection since it was discovered.…”
Section: Introductionmentioning
confidence: 99%
“…The spread of BMSB populations is threatening a wide range of economic crops (Leskey & Nielsen, ). It has spurred to develop various management options including pheromone‐based monitoring and trapping (Khrimian et al, ), biological control utilizing entomopathogenic fungi (Gouli et al, ), and a recent RNA interference (RNAi)‐mediated approach (Ghosh, Hunter, Park, & Gundersen‐Rindal, , ).…”
Section: Introductionmentioning
confidence: 99%